2023
DOI: 10.3390/agronomy13082182
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Application Alleviates the Negative Effects of Deficit Irrigation and Improves Growth Performance, Essential Oil Yield and Water-Use Efficiency of Mint Crop

Christina Chaski,
Kyriakos D. Giannoulis,
Alexios A. Alexopoulos
et al.

Abstract: The scarcity of water is limiting crop production and is one of the most important stressors that severely affects crop yield, and it may also decrease the quality of the final products. Most of the medicinal and aromatic plants are considered resilient to water stress and constitute a sustainable choice for crop production in arid and semiarid conditions. In the present study, we examined the effect of scheduled deficit irrigation (e.g., I1: 40% of field capacity); I2: 70% of field capacity; and I3: 100% of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The enhancement in the flowering and chemical compositions were found in lily plants received Humicil compared to untreated plants as may be related to the enhancements in the vegetative growth, which in turn improved nutrients uptake and photosynthesis by the plants, then induced the flowering and chemical components (Nasiri et al, 2021;Ampong et al, 2022). In this respect, results of Chaski et al (2023) proved that bio stimulants that contained seaweed extracts and humic acids improved growth, yield and chemical components of mint crop. The results of Rahbar et al (2023) indicated that foliar spraying with humic acid contributed to increase the carbohydrate rate of the olive leaves.…”
Section: Discussionmentioning
confidence: 90%
“…The enhancement in the flowering and chemical compositions were found in lily plants received Humicil compared to untreated plants as may be related to the enhancements in the vegetative growth, which in turn improved nutrients uptake and photosynthesis by the plants, then induced the flowering and chemical components (Nasiri et al, 2021;Ampong et al, 2022). In this respect, results of Chaski et al (2023) proved that bio stimulants that contained seaweed extracts and humic acids improved growth, yield and chemical components of mint crop. The results of Rahbar et al (2023) indicated that foliar spraying with humic acid contributed to increase the carbohydrate rate of the olive leaves.…”
Section: Discussionmentioning
confidence: 90%
“…In biostimulated plants a decrease of these parameters was observed compared to control plants. It is commonly known that stressful conditions affect MAPs capacity to create secondary metabolites ( Figueiredo et al., 2008 ; Tawfeeq et al., 2016 ; Kulak et al., 2020 ; Chaski et al., 2023 ; Farruggia et al., 2023 ). Presumably, the foliar biostimulant treatments and the rains that fell during the last stage of the cycle, before the sample collection, helped the sage plants evade stress situations and consequently lower the production of some secondary metabolites, like phenols and rosmarinic acid.…”
Section: Discussionmentioning
confidence: 99%